Introducing "Physics of music" to students using free software - Pothiyodath, Nishanth; Murkoth, Udayanandan Kandoth (Momentum: Physics Education Journal, 2022)
Many consider physics to be a highly mathematical oriented subject to study. To break this opinion and also to generate a deep interest in physics, a course on ‘Physics of Music’ can be introduced at any level of a curriculum. We present a simple and practical way of introducing this topic even for school level students. Teachers, along with students, can visualise and feel physics all time throughout the course.